Antiferroelectric Thin Films: Giant Negative Electrocaloric Effect in Antiferroelectric La‐Doped Pb(ZrTi)O3 Thin Films Near Room Temperature (Adv. Mater. 20/2015). (May 2015) - Geng, Wenping; Liu, Yang; Meng, Xiangjian; Bellaiche, Laurent; Scott, James F.; Dkhil, Brahim; Jiang, Anquan
<x xml:space="preserve">Abstract</x> On page 3165, Y. Liu and co‐workers demonstrate a giant negative electrocaloric effect (ECE) in antiferroelectric La‐doped Pb(ZrTi)O3 hin films near room temperature. possible mechanism of negative ECE in antiferroelectrics is proposed. One potential application for this negative ECE is to combine with conventional ECE to enhance further the cooling efficiency.